Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ehj.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and ABO blood-groups in Africans. Are blood-group A individuals at higher risk of ischemic disease?: A pilot study

Abstract: BackgroundSince the discovery of the ABO blood group system by Karl Landsteiner in 1901, several reports have suggested an important involvement of the ABO blood group system in the susceptibility to thrombosis. Assessing that non-O blood groups in particular A blood group confer a higher risk of venous and arterial thrombosis than group O.Epidemiologic data are typically not available for all racial and ethnics groups.The purpose of this pilot study was to identify a link between ABO blood group and ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(21 reference statements)
2
7
4
1
Order By: Relevance
“…In addition, other studies have suggested that the A blood group is an independent risk factor for coronary atherosclerosis and ischemic CVD. 2,32,33 In contrast to previous studies, MPV, a useful prognostic marker in patients with CAD and venous thrombosis, was found to be significantly lower in A blood group subjects than in B and AB blood group subjects (P = 0.024 and P = 0.007, respectively).…”
Section: Similarly No Relationship Was Observed Between Abo Groups Andcontrasting
confidence: 94%
“…In addition, other studies have suggested that the A blood group is an independent risk factor for coronary atherosclerosis and ischemic CVD. 2,32,33 In contrast to previous studies, MPV, a useful prognostic marker in patients with CAD and venous thrombosis, was found to be significantly lower in A blood group subjects than in B and AB blood group subjects (P = 0.024 and P = 0.007, respectively).…”
Section: Similarly No Relationship Was Observed Between Abo Groups Andcontrasting
confidence: 94%
“…Anstee [29] reported that an association between blood group and CVD risk may only exist with non-O blood subtypes. Contrary to our findings, it was reported in a study performed in Senegal that the incidence of ischemic CVD in men was significantly higher in blood group A [23]. In the context of CVD in general, the level of risk of CVD associated with different ABO subtypes observed in our study, especially in blood group O, may not, in fact, differ from the study done in Senegal.…”
Section: Discussioncontrasting
confidence: 99%
“…The level of CVD risk among females did not differ significantly between groups; however, among male subjects, the level of CVD risk in members of blood group O was significantly increased compared to non-O blood groups. This finding is consistent with prior studies reporting evidence of an association between ABO blood subtypes and risk of CVD [10,13,17,18,21,[23][24][25][26][27]. However, there is inconsistency in these prior findings as to which ABO blood subtype is at greater risk of CVD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations